Performances Body Dimensions of Bali Cattle of Traditional Livestock in Southeast Sulawesi - Hafid, Harapin (Indonesian Journal of Agricultural Research, 2020)
This study aims to determine the comparison of body measurements and body weight of male and female Balinese cows. The research was at the Kendari City Slaughterhouse. Measuring 94 Bali cows consisting of 47 males and 47 females aged 1-3 years. Data were analyzed by Student's T-test. The results showed that the average male body weight was 191.30 kg and female 181.98 kg. The average body measurements of male and female Balinese cows are body length (114.11 cm and 110.15 cm), gumba height (111.68 cm and 109.60 cm), chest circumference (149.30 cm and 146.15 cm), front canon bone circumference (14.89 cm and 14.75 cm), rear canon bone circumference (16.67 cm and 16.63 cm). Where there is no significant difference in linear body measurements in the two sexes of cattle (p> 0.05). It was concluded that the linear measurements of the bodies of Balinese male and female cattle from traditional livestock breeding in Sulawesi Sulawesi were relatively uniform. But quantitatively the body measurements of male Bali cattle are relatively higher compared to female Bali cattle.